Effet du type dianticoagulant, de la duree et de la temperature de conservation, et de l'azide de sodium sur la teneur en progesterone du sang - Inns, J.H.; Cecchini, G.; Mattoni, M. (1989)
Determines the effects of anticoagulant, storage time, storage temperature and sodium azide on blood progesterone concentrations in order to develop practical guidelines for the collection of Zebu blood under tropical conditions.